Teaching grammar by using technologies: Unlocking language pedagogical potential - Aisyiyah, Siti; Novawan, Adriadi; Dewangga, Vigo; Bunarkaheni, Suyik (Politeknik Negeri Jember, 2024)
Language learning is a complex cognitive process which involves mastering various linguistic components, with grammar serving as a fundamental pillar. Traditionally, grammar instruction relied on rote memorization and textbook exercises, often divorcing learners from real-life language use. This paper explores the transformative impact of technology on grammar pedagogy, addressing the limitations of traditional methods. The integration of digital tools, gamification, virtual learning environments, and adaptive systems has redefined grammar instruction, fostering dynamic and engaging learning experiences. The paper discusses the implications for both students and teachers, emphasizing the need for a balanced approach that harmonizes tradition and technology. Recommendations for future research highlight emerging trends and the evolving landscape of technology-enhanced grammar education.